Human Rights in the Projection of Constitutionalism and the Indonesian Legal State: Hak Asasi Manusia dalam Proyeksi Konstitusionalisme dan Negara Hukum Indonesia - Afoeli, La Ode Muhammad Taufiq (Sangia Nibandera Law Research, 2024)
This study examines the relationship between human rights, constitutionalism, and the rule of law within the framework of the 1945 Constitution of the Republic of Indonesia. Using a normative juridical approach, this study analyzes primary and secondary legal sources to understand the integration of human rights in the Indonesian legal system. A historical approach is used to trace the development of the concept of human rights in the history of national constitutionalism, while a conceptual analysis is conducted to describe the correlation between human rights, Pancasila values, and the principles of the rule of law. The results of the study show that human rights in Indonesia not only reflect universal principles, but also moral and national values ​​that make it more than just individual freedom, but also a dignified independence. This study emphasizes that the fulfillment of human rights is an essential element in building a just and civilized rule of law state in accordance with the spirit of Pancasila.